Mangrove potential and community characteristics for strengthening the utilization of environmental services based on ecotourism: A case study in Karangsong, Indramayu, West Java. Issue 1 (November 2021) - Garsetiasih, R; Takandjandji, M; Gunawan, H; Yuskianti, V; Karlina, E
Abstract: Mangrove rehabilitation is often challenged by a lack of support from local communities. The success of mangrove rehabilitation can increase the chances of success by increasing the local economy, which will help increase public awareness. This study was conducted in the mangrove forest of Karangsong Village with the aim to identify the potential of mangroves and the characteristics of local communities as capital for the use of environmental services based on mangrove ecotourism. The interview method with semi-structured guidelines was applied to obtain social, economic and public perceptions data. Karangsong mangrove forest is dominated by three species of mangroves, namely Rhizophora mucronata, Rhizophora stylosa and Rhizophora apiculate. It has also become a habitat for various bird species such as javan pond heron, wandering whistling duck, lesser adjutant, imperial pied pigeon, and common sandpiper, which are potential ecotourism objects. The results showed that positive perceptions derived from the economic benefits obtained from mangroves, which have become feedback for mangrove conservation. The role of the driving group is also crucial to maintain the consistency of stakeholders' enthusiasm to conserve mangroves. Sustainable ecotourism development needs to involve local communities in its management.